2009
DOI: 10.1126/science.1177373
|View full text |Cite
|
Sign up to set email alerts
|

The Transmissibility and Control of Pandemic Influenza A (H1N1) Virus

Abstract: Pandemic influenza A (H1N1) 2009 (pandemic H1N1) is spreading throughout the planet. It has become the dominant strain in the southern hemisphere, where the influenza season is underway. Here, based on reported case clusters in the USA, we estimate the household secondary attack rate for pandemic H1N1 to be 27.3% (95% CI: 12.2%-50.5%). From a school outbreak, we estimate a school child infects 2.4 (95% CI: 1.8-3.2) other children within the school. We estimate the basic reproductive number, R 0 , to range from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
453
3
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(510 citation statements)
references
References 24 publications
40
453
3
9
Order By: Relevance
“…In the range β ∈ [1. 5,4] and for N = 2000, subject to t * , the fastest spreading is about twofold faster than the slowest one in Fig. 4(d), while in Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In the range β ∈ [1. 5,4] and for N = 2000, subject to t * , the fastest spreading is about twofold faster than the slowest one in Fig. 4(d), while in Fig.…”
Section: Resultsmentioning
confidence: 78%
“…infectivities of biological virus [4,5] and the multi-dimensional infection mechanisms of mobile virus [6]. Recently, quantitative understanding of human behavior has refined the traditional models and results [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In a study in Kenya the secondary household transmission was found to be 26% [27]. The transmissibility in schools has been found to be around 20% [28]. The incubation period is between 1 and 7 days and an infected person can transmit the infection from a day prior to onset of symptoms to a day after symptoms have subsided.…”
Section: Mode Of Transmission and Incubation Periodmentioning
confidence: 99%
“…Current S-OIV (2009 H1N1 influenza virus) is a triple reassortment (in terms of host-origin) of influenza gene segments, with PA and PB2 from avian, PB1 from human and HA, NP, NS, NA and M from classical/Eurasian swine (Dawood et al, 2009;Smith et al, 2009;Gao and Sun, 2010). This current H1N1 virus has been found to have many similar properties to the 1918 pandemic H1N1 virus, including the overall similarity of the genome and characteristics of pathogenesis (Itoh et al, 2009;Shen et al, 2009;WHO, 2009;Yang et al, 2009;Igarashi et al, 2010;Yeping Sun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%